2003
DOI: 10.1021/jm030114w
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Phenyl Ring Disubstitution on Bisbenzimidazole and Terbenzimidazole Cytotoxicity:  Synthesis and Biological Evaluation as Radioprotectors

Abstract: DNA minor groove binders, Hoechst 33258 and Hoechst 33342, have been reported to protect against radiation-induced DNA-strand breakage, but their mutagenicity and cytotoxicity limit their use as protectors of normal tissue during radiotherapy and as biological radioprotectors during accidental radiation exposure. On the basis of these observations, two new nontoxic disubstituted benzimidazoles were synthesized, one having two methoxy groups (5-(4-methylpiperazin-1-yl)-2-[2'-(3,4-dimethoxyphenyl)-5'-benzimidazo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
60
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 57 publications
(120 reference statements)
0
60
0
Order By: Relevance
“…In order to understand the mechanism involved for in vivo radioprotection, an ORAC-FL assay was performed to study the antioxidant capacity of DMA to cement the already proven free radical scavenging property of DMA (Tawar et al, 2003). This assay measures the loss of fluorescein fluorescence over time due to the peroxyl-radical formation by the breakdown of 2,2ʹ-azobis(2-amidino-propane) dihydrochloride (AAPH).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to understand the mechanism involved for in vivo radioprotection, an ORAC-FL assay was performed to study the antioxidant capacity of DMA to cement the already proven free radical scavenging property of DMA (Tawar et al, 2003). This assay measures the loss of fluorescein fluorescence over time due to the peroxyl-radical formation by the breakdown of 2,2ʹ-azobis(2-amidino-propane) dihydrochloride (AAPH).…”
Section: Discussionmentioning
confidence: 99%
“…DMA was synthesized, characterized, and converted to its hydrochloride salt to make it water soluble and purified by highperformance liquid chromatography (HPLC) as per the procedure reported elsewhere (Tawar et al, 2003) (Fig. 1).…”
Section: Chemicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…13 We have synthesized several analogues of Hoechst 33342 with dichloro {DCA, 2-(2,4-dichlorophenyl)-5-[5-(4-methylpiperazin-1-yl)-1H-benzimidazol-2-yl]-1H-benzimidazole} and difluoro {DFA, 2-(2,4-difluorophenyl)-5-[5-(4-methylpiperazinyl)-1H-benzimidazol-2-yl]-1H-benzimidazole} substitutions on the phenyl ring and evaluated their activity against HuTOPI (Figure 1). 14 In the present study, we have evaluated DCA, DFA and DMA for their antibacterial activity against standard E. coli and resistant, clinical strains of E. coli isolated from UTI patients. The MIC and MBC study showed that DMA is more active against most of the resistant E. coli strains.…”
Section: Introductionmentioning
confidence: 99%
“…8,9) Our group has also studied cellular responses of a few synthesized bisbenzimidazole derivatives in in-vitro systems. 10,11) Hoechst 33258 is a bisbenzimidazole molecule that binds strongly in the minor groove region of duplex DNA with predominant specificity for AT rich sequences. [12][13][14] Bisbenzimidazole compounds have also been reported to increase radiation induced cytotoxicity in several cancerous cell lines 15) and thus have an ability to improve radiotherapy.…”
mentioning
confidence: 99%